2018
DOI: 10.1021/acs.langmuir.7b03386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of the Hydration Behavior of a Zwitterion Brush Array and Its Antifouling Property in an Aqueous Environment

Abstract: We carried out umbrella sampling and molecular dynamics (MD) simulations to investigate molecular interactions between sulfobetaine zwitterions or between sulfobetaine brushes in different media. Simulation results show that it is more energetically favorable for the two sulfobetaine zwitterions or brushes to be fully hydrated in aqueous solutions than in vacuum where strong ion pairs are formed. Structural properties of the hydrated sulfobetaine brush array and its antifouling behavior against a foulant gel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 78 publications
5
54
0
Order By: Relevance
“…Similarly, except for the peak of 0.38–0.5 nm of SB 2C ‐SAM ~ SB 6C ‐SAM, the other peaks represent that the distance between N and O within the single SB molecule (see the inset pictures of Figure 12b–f). Similar experimental results can be found in the work of Xiang et al 62 They found the similar result that the distance between the quaternary ammonium C atoms and the sulfonate O atoms within a single sulfobetaine zwitterion branch (CSL = 2) is in the range of 0.5–0.6 nm, while the distance between the two in an ion pair is about 0.3–0.35 nm. Compared with the NO RDFs in pure water, these peaks of cationic and anionic groups in salt solution (red line) get lower with the increase of CSL, especially when CSL = 3–6.…”
Section: Resultssupporting
confidence: 89%
“…Similarly, except for the peak of 0.38–0.5 nm of SB 2C ‐SAM ~ SB 6C ‐SAM, the other peaks represent that the distance between N and O within the single SB molecule (see the inset pictures of Figure 12b–f). Similar experimental results can be found in the work of Xiang et al 62 They found the similar result that the distance between the quaternary ammonium C atoms and the sulfonate O atoms within a single sulfobetaine zwitterion branch (CSL = 2) is in the range of 0.5–0.6 nm, while the distance between the two in an ion pair is about 0.3–0.35 nm. Compared with the NO RDFs in pure water, these peaks of cationic and anionic groups in salt solution (red line) get lower with the increase of CSL, especially when CSL = 3–6.…”
Section: Resultssupporting
confidence: 89%
“…Xiang et al carried out umbrella sampling and molecular dynamics (MD) simulations, and showed that the higher grafting density sulfobetaine brush array exhibits a more organized structure which can hold a tightly bound hydration water layer at the interface. [ 61 ] Compression of this hydration layer results in a strong repulsive force. However, at a lower grafting density, the brush array exhibited a randomly oriented structure in which the repelling of the brush array was through the deformation of the sulfobetaine branches.…”
Section: Biomimetic Antifouling Surface Technologiesmentioning
confidence: 99%
“…[7][8][9] Among non-biocidal layers-which are considered to be less toxic 7 -one can find materials that are antifouling because of surface structuration (such as super-slippery sharklet technology), 10 or superhydrophobicity, 11,12 or high surface hydrophilicity. 13 Among hydrophilic, non-biocidal coatings, zwitterionic polymers [14][15][16][17][18][19][20][21][22] are considered as one of the two major classes of antifouling materials that are accessible and relatively easy to implement, the other being hydrophilic polymers based on poly(ethylene glycol) (PEG). 23,24 Brushes of zwitterionic polymers terminally grafted to a surface have been found to be effective antifouling agents, exhibiting higher chemical stability than PEG-based layers.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade there have been several atomistic 16,[19][20][21][22] and a few mesoscopic 25 simulations of the antifouling action of zwitterionic membranes. In a series of papers, Shao et al examine the influence of charged groups 16 and ions 20 on polyzwitterions, as well as the effect of the latter on proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation